HAKIKAT PENDIDIKAN DAN POLA KEPEMIMPINAN TERHADAP KINERJA ANGGOTA DPRD - Moh. Shaleh; Sugeng Rusmiwari; Dody Setyawan (Universitas Tribhuwana Tunggadewi, 2015)
Abstract: In fact, the committee of DPRD (municipal level) who had been trusted by society in capacity,authority, and capability build good generation especially in gevernment education. It could create the vice of society in right way so they could not be falsehood as leader to the society. On the other hand, education was the first foundation for committee DPRD (municipal level) that could prove the soul of leader to the society. This research used quantitative descriptive withcase studi which used technique samling and the sample 60 persons. Next the analysis data used SPSS, validity testing, Alpha Crobach reability and double linear regression testing. From this research showedthat therewas significance positive influence difference between Hakikat Pendidikan Dan Pola Kepemimpinan (education and leadership system) to the committee PRD’s (municipal level) working. It showed from their value in working of the quantity and quality of the committee DPRD’s (municipal level) that was good. Finally committee DPRD’s (municipal level) in Sumenep had good achievement and requirement that needed for the Sumenep society. Key Words : Education Reality, Leadership Pattern, Council Member Performan Delegation of Area